Thyroid autoimmunity in children and adolescents with newly diagnosed type 1 diabetes mellitus - Eui Seok Jung; Dong Kyun Han; Eun Mi Yang; Min Sun Kim; Dae-Yeol Lee; Chan Jong Kim (Korean Society of Pediatric Endocrinology, 2014)
PurposeThis study aim to investigate the occurrence of autoimmune thyroid disease in children and adolescents at onset of type 1 diabetes mellitus (T1DM) and to assess whether the presence of diabetes-specific autoantibodies can predict the autoimmune thyroid disorder.MethodsSeventy-three children with T1DM were recruited. Glutamic acid decarboxylase antibodies (GADA), islet cell antibodies (ICA), insulin autoantibodies (IAA), and thyroid antibodies were determined in all patients at the time of diagnosis.ResultsThe majority of patients (87.7%) had at least one pancreatic antibody (74.0% for GADA, 20.5% for ICA, and 24.7% for IAA). Thyroid autoantibodies were found in 19 of 73 patients (26.0%) at diagnosis. Thyroid autoimmunity (TA) incidence was not statistically significant by GADA or ICA positivity, but significantly higher by IAA positivity (P=0.03), and IAA positivity showed odds ratio, 4.931; 95% confidence interval, 1.323-18.381 for TA.ConclusionThe IAA positivity in children and adolescents with TIDM was strongly related to positivity of thyroid autoantibodies and thus it could serve as an index for early prediction of the development of the thyroid autoimmune disorder among children and adolescents with TIDM.